Lumbar Total Disk Replacement Device Removals and Revisions Performed During a 20-Year Experience with 2141 Patients - Guyer, Richard D; Blumenthal, Scott L; Shellock, Jessica L; Zigler, Jack E; Ohnmeiss, Donna D (Spine (Philadelphia, Pa. 1976), 2024)
This was a retrospective study with prospective patient contact attempted to collect current data. The purpose was to investigate the incidence and reasons for lumbar total disk replacement (TDR) removal or revision. A concern regarding lumbar TDR was safety, particularly the need for device removal or revision. This may be particularly important considering removal/revision requires repeat anterior exposure with an increased risk of vascular injury. Data were collected for a series of 2141 lumbar TDR patients, beginning with the first case experience in 2000. The mean follow-up was 78.6 months. For each case of device removal/revision, the reason, duration from index surgery, and procedure performed were recorded. Of 2141 patients, 27 (1.26%) underwent TDR removal or revision. Device removal was performed in 24 patients (1.12%), while three patients underwent revision (0.14%). Of the 24 removals, 12 were due to migration and/or loosening, three developed problems post-trauma, two developed lymphocytic reaction to device materials, two had ongoing pain, and there was one case of each: TDR was too large, vertebral body fracture (osteoporosis), lytic lesion, device subsidence and facet arthrosis, and infection seeded from a chest infection 146 months post-TDR. The three revisions were for Core repositioning (technique error), device repositioning after displacement, and core replacement due to wear/failure. With respect to timing, 37.0% of removals/revisions occurred within one-month postimplantation. Of note, 40.7% of removals/revisions occurred in the first 25 TDR cases performed by individual surgeons. There was one significant vascular complication occurring in a patient whose TDR was removed due to trauma. This was also the only patient among 258 with ≥15-year follow-up who underwent removal/revision. In this large consecutive series, 1.26% of TDRs were removed/revised. The low rate over a 20 year period supports the safety of these devices.